Grandad's camper - Woodgate, Harry (New York, NY : Little Bee Books, 2021)
A child who enjoys Grandad's stories of his travels and adventures with Gramps persuades him to fix up their old camper and take another trip, in honor of Gramps.
School Library Journal starred, June 2021
Publishers Weekly, April 2021
Kirkus Starred, March 2021
4.3
K-3
Keywords: Voyages and travels -- Juvenile fiction; Grandfathers -- Juvenile fiction; Gays -- Juvenile fiction; Adventure stories; Voyages and travels -- Fiction; Grandfathers -- Fiction; Gays -- Fiction; Adventure and adventurers -- Fiction; Action and adventure fiction; LGBTQ+ picture book